1984
DOI: 10.1002/mrd.1120090203
|View full text |Cite
|
Sign up to set email alerts
|

Human sperm motility after migration into, and incubation in, synthetic media

Abstract: Ten framesisec microcinematography ("film"), 1 second timed-exposure photomicrography ("photo"), and laser Doppler velocimetry (LDV) were used to analyse the swimming patterns of human spermatozoa after migration (1 h at 37°C) into an overlying layer of either BWW or Menezo's B2 media. The upper layer of medium was carefully removed and further incubated at 37°C for either 4 h (B2) or 5 h (BWW) and the spcrm motility analysed again. Five experiments were performed using semen from different donors. Film and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 26 publications
2
33
1
Order By: Relevance
“…Similarly, the preimmune serum and the anti-P26h antiserum did not affect the percentage of motile spermatozoa nor their movement characteristics, especially the velocity, linearity, and the amplitude of lateral head displacement (ALH). These three parameters have been reported to be important contributors to sperm hyperactivation, an integral part of capacitation that precedes sperm binding to the zona pellucida and the acrosome reaction [33,47,48]. Taken together, these results suggest that the polyclonal antibodies inhibited spermzona pellucida interaction in the human without affecting sperm capacitation.…”
Section: Discussionmentioning
confidence: 54%
“…Similarly, the preimmune serum and the anti-P26h antiserum did not affect the percentage of motile spermatozoa nor their movement characteristics, especially the velocity, linearity, and the amplitude of lateral head displacement (ALH). These three parameters have been reported to be important contributors to sperm hyperactivation, an integral part of capacitation that precedes sperm binding to the zona pellucida and the acrosome reaction [33,47,48]. Taken together, these results suggest that the polyclonal antibodies inhibited spermzona pellucida interaction in the human without affecting sperm capacitation.…”
Section: Discussionmentioning
confidence: 54%
“…However, it is possible that the antibodies affect velocity, amplitude of lateral head displacement, and beat frequency. These parameters have been reported to be important contributors to hyperactivation of sperm cells, which is considered an integral part of capacitation that precedes the acrosome reaction and sperm binding to the zona pellucida of the oocyte [26,27]. This may be one of the mechanisms by which antibodies affect sperm function (i.e., capacitation, acrosome reaction, and sperm-oocyte binding).…”
Section: Discussionmentioning
confidence: 96%
“…The addition of HSA at a level of 0.8% had no effect on the chromatin stability, whereas it has been shown that HSA at a level of 4% removes divalent cations such as Zn" in the same way as EDTA does and that 4% HSA is a suitable decondensing reagent [ 7 ] . Thus it is shown that these milieux, which select motile and morphologically normal population of spermatozoa [9] and which allow capacitation of the spermatozoa [ I ] , have no effect on the chromatin stability of the spermatozoa.…”
Section: Discussionmentioning
confidence: 99%
“…A population of spermatozoa, selected by a swimup migration in a synthetic medium that improves morphology and motility [9] and incubated under conditions reported to sustain capacitation [ 11 , was tested by using a nuclear chromatin decondensation ability test [S] .…”
Section: Introductionmentioning
confidence: 99%